Implementation of A Transformative Learning Model in Supervising Non Formal Education Institution in the Submission of Accreditation - Fuad Hasan; Arief Tukiman Hendrawijaya; Lutfi Ariefianto (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
PKBM Sumber Ilmu, The partner of this community services has failed to pass the first steps of pursuing the accreditation. The cause of this failure is that the formal education mindset is still embedded in the managers and educators which influence the pattern of preparing accreditation documents. As the result, the document was not satisfy the assessor which assesst the requirement. This community services try to provide supervission for the managers and tutors of PKBM Sumber Ilmu so they can (1) prepare accreditation documents that are in accordance with the characteristics of non-formal education, and (2) prepare maximum supporting evidences for fields assessment. This program implement transformative learning and andragogy approach which incude two main activities namely workshop and assessment simmulation. The stage of activities are providing material related to accreditation documents and evidences of field assessment for non-formal education units, providing assistance to make sure the suitability of the documents and evidences, and carry out field assessment. The result of this community services are (1) the achievement of the accredation documents reach more than 80%, and (2) the readiness of supporting evidence for field assessment reach 80%. Because of those result, the PKBM Sumber Ilmu are ready for the whole accreditation process.